(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Sleep is a fundamental biological process essential for physical, cognitive, and emotional wellbeing. Across history, cultures have interpreted sleep in diverse ways, yet modern scientific research consistently demonstrates its central role in mental health, physiological restoration, and daily functioning. This paper integrates historical perspectives, physiological mechanisms, mental health associations, and lifestyle interventions by synthesizing two comprehensive documents on sleep. Evidence from psychiatric research, sleep science, and behavioral health demonstrates that sleep disturbances both contribute to and result from mental health disorders, forming a bi‑directional relationship. The review concludes with practical strategies for improving sleep quality and reducing the burden of sleep related dysfunction.